Benchmarking Vended Authority Control Practices in ARL Libraries. Issue 4 (2nd October 2018) - Mugridge, Rebecca L.; Nous, Rebecca; Poehlmann, Nancy; West, Wendy
ABSTRACT: This article presents the results of a survey designed to benchmark the use of vendors to support authority control activities in Association of Research Libraries member libraries. Such activities include updating authority or bibliographic records, sourcing authority records, participation in cooperative cataloging efforts, and more. The survey investigated whether and how responding libraries used vendors to create and maintain an authority file and process current cataloging records. The survey gathered demographic and other information about the libraries, and the authors sought to identify trends and correlations between these and other factors.